2020
DOI: 10.3390/ijms21103734
|View full text |Cite
|
Sign up to set email alerts
|

Adherent-Invasive E. coli: Update on the Lifestyle of a Troublemaker in Crohn’s Disease

Abstract: Besides genetic polymorphisms and environmental factors, the intestinal microbiota is an important factor in the etiology of Crohn’s disease (CD). Among microbiota alterations, a particular pathotype of Escherichia coli involved in the pathogenesis of CD abnormally colonizes the intestinal mucosa of patients: the adherent-invasive Escherichia coli (AIEC) pathobiont bacteria, which have the abilities to adhere to and to invade intestinal epithelial cells (IECs), as well as to survive and replicate within macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 194 publications
(229 reference statements)
0
55
0
Order By: Relevance
“…E. faecalis infection induces superoxide production, which damages DNA in epithelial cells (50,52). Although Escherichia coli (E. coli) is a gut commensal bacterium, studies have reported higher levels of colonic colonization by mucosa-associated E. coli in CRC patients compared with that in healthy people (53,54,58). Yu et al found Peptostreptococcus anaerobius (P. anaerobius) was significantly enriched in fecal and mucosal microbiotas from patients with CRC (55,56).…”
Section: Intestinal Microbiota In Crcmentioning
confidence: 99%
“…E. faecalis infection induces superoxide production, which damages DNA in epithelial cells (50,52). Although Escherichia coli (E. coli) is a gut commensal bacterium, studies have reported higher levels of colonic colonization by mucosa-associated E. coli in CRC patients compared with that in healthy people (53,54,58). Yu et al found Peptostreptococcus anaerobius (P. anaerobius) was significantly enriched in fecal and mucosal microbiotas from patients with CRC (55,56).…”
Section: Intestinal Microbiota In Crcmentioning
confidence: 99%
“…1 Tissues from patients with IBD often have increased numbers of Escherichia coli compared with those from healthy individuals, 2 and a subgroup therein, the adherent-invasive E coli (AIEC), has emerged as pathobionts. 3,4 Attaching via pili and long polar fimbriae, 5,6 AIEC can cause reactive oxygen species (ROS) and proinflammatory cytokine production by epithelial cells 7,8 and increase epithelial permeability. 9 AIECs have enhanced survival within macrophages, 10 and can exaggerate the severity of murine colitis.…”
Section: Q7 Q8 Q9mentioning
confidence: 99%
“…The most recurring and contrasted finding is the increase of adherent-invasive E. coli in the gut of IBD patients; this infectious agent is able to adhere to and cross the intestinal mucus barrier, invading the gut epithelial layer. Moreover, this species is capable of surviving and replicating in macrophages, leading to TNFα secretion and inflammation [ 92 , 120 ].…”
Section: Gut Dysbiosis In Inflammatory Bowel Diseasementioning
confidence: 99%